Trade Relations Between Paraguay and The European Union: Effects of The Generalized System of Preferences Plus (1999-2018) - Cáceres-Benítez, Marcos David (2023)
This research aims to determine the effects of the Generalized System of Preferences Plus (GSP+) in the relations between Paraguay and the European Union (EU) from 1999-2018. The methodology followed was bibliographic-documentary research, with a quantitative approach. The main results indicate that, compared  to the generalized preference schemes, the EU GSP + showed excellent results. In addition, trade relations during the validity of the system in question had a substantial increase, in terms of the level and diversification of exports. Likewise, the coefficient estimated in the model to show the effect of SGP+ was positive and its magnitude was the highest of the variables analyzed in the model.